Mineral casting prepared based on modified epoxy resin
By combining modified bisphenol A epoxy resin and reinforced curing agent, combined with specific dibasic acid and nanosilicon dioxide, mineral castings with high damping ratio and shock absorption properties are prepared, solving the insufficient performance problem of existing mineral castings when used in high-end industrial master machines, and achieving higher heat resistance, compressive strength, and lower production costs and energy consumption.
Patent Information
- Application Number
- CN202411646377.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
When used in high-end industrial master machines, existing mineral castings have problems such as low damping performance, limited precision retention time, high cost, high exhaust gas pollution and energy consumption. The heat resistance, weather resistance and toughness of epoxy resins are insufficient, which affects its application in the field of high-end industrial master machines.
Using a modified bisphenol A epoxy resin solution and a reinforced curing agent, combined with specific dibasic acids and nanosilicon dioxide, mineral castings with high thermal expansion coefficient, strong temperature resistance, compressive strength and internal bonding strength are prepared through specific process steps such as stirring, heating curing and post-curing treatment.
The high damping ratio and shock absorption performance of mineral castings are achieved, and their application performance in high-end industrial master machines is improved, including longer precision retention time, higher heat resistance and compressive strength, and reduced production costs and energy consumption.
Smart Images

Figure BDA0005139799660000081 
Figure BDA0005139799660000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mineral castings, and in particular relates to a mineral casting prepared based on modified epoxy resin. Background Art
[0002] Currently, high-end intelligent industrial machine tools on the market mostly use cast iron as the main material, but their damping performance is low, the accuracy retention time is limited, and the cost is high. At the same time, waste gas pollution and high casting energy consumption will be generated during the production process, which does not meet environmental protection requirements and limits the further improvement of high-end industrial machine tools in terms of accuracy and environmental protection.
[0003] Mineral casting is a new type of environmentally friendly material. It uses natural granite fragments and scraps as the main raw materials, and adds thermosetting epoxy resin and curing agent. It is a new type of mineral casting prepared by mixing, stirring and vibrating.
[0004] Epoxy resin has the characteristics of high density, low shrinkage during curing and corrosion resistance, but it also has problems with heat resistance, weather resistance and poor toughness. Poor heat resistance will affect the precision maintenance ability of mineral castings, weather resistance will affect the service life of mineral castings, and poor toughness will affect the service life of mineral castings while also affecting their impact resistance. These problems will greatly affect the application of mineral castings in the field of high-end industrial mother machines, so epoxy resin needs to be modified.
[0005] At the same time, current curing agents such as amine curing agents have the following problems: fast curing speed, strong volatility and low heat resistance of the cured resin. On the one hand, the fast curing speed will make the curing reaction more intense and release a large amount of heat. The strong volatility will produce more bubbles inside the epoxy resin, affecting the performance of the epoxy resin after curing. At the same time, the fast curing speed will also make the components of the mineral casting have less time to mix evenly, affecting the uniformity of the mineral casting, thereby affecting the various properties of the mineral casting. Summary of the invention
[0006] The object of the present invention is to provide a mineral casting prepared based on modified epoxy resin.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention comprises the following steps:
[0008] A mineral casting prepared based on modified epoxy resin, comprising the following components by weight:
[0009] 5.4-5.8 parts of modified bisphenol A epoxy resin solution, 6.4-6.8 parts of enhanced curing agent, 56.6-57 parts of aggregate, 30.8-31.2 parts of filler, the specific preparation steps are:
[0010] Firstly, the enhanced curing agent is dissolved in 6% to 8% of dimethyl sulfoxide by weight and stirred evenly, then added into the modified bisphenol A epoxy resin solution and stirred evenly, then the aggregate and filler are added and stirred evenly, then the temperature is raised to 75 to 80°C for curing for 7.5 to 8.5 hours, then the temperature is further raised to 95 to 100°C for post-curing treatment for 2 to 3 hours, then the mineral casting is obtained after cooling to room temperature for curing for 7 to 8 hours.
[0011] Wherein, the preparation steps of the modified bisphenol A epoxy resin solution are:
[0012] (1) mixing bisphenol A epoxy resin and active diluent octyl glycidyl ether in a mass ratio of 74-76:24-26 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0013] (2) mixing the dibasic acid and the organic solvent dimethyl sulfoxide in a mass ratio of 1:24-26, and obtaining a dibasic acid solution after the dibasic acid is completely dissolved;
[0014] (3) A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 90.8-91:9-9.2, and the mixture is placed in a flask and placed in a magnetically controlled stirring oil bath for uniform mixing. At 100° C., 0.8% to 1% by mass of the catalyst triphenylphosphine of the bisphenol A epoxy resin is added and slowly stirred until uniform. The mixture is then heated to 130° C. and slowly stirred for reaction for 3 hours. Finally, 0.8% to 1% by mass of the dispersed nano-silica of the bisphenol A epoxy resin is added to obtain a modified bisphenol A epoxy resin solution.
[0015] The dibasic acid is specifically 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid.
[0016] Wherein, the preparation method of dispersed nano silicon dioxide is:
[0017] Anhydrous ethanol and deionized water are mixed in a volume ratio of 3 to 4:1 and the pH value is adjusted to 5.4 to 5.6 to obtain a solvent, then 2 to 3 parts by mass of nano-silicon dioxide are immersed in the solvent and stirred evenly, then 4% to 5% by mass of isopropoxy dioleic acid acyloxy (dioctyl phosphate acyloxy) titanate is added, the system is heated to 46 to 50°C and reacted under 300W ultrasonic conditions for 50 to 60 minutes, after the reaction, the modified nano-silicon dioxide is washed with anhydrous ethanol and dried to obtain modified nano-silicon dioxide, and then the modified nano-silicon dioxide and octadecyl alcohol polyether stearate are evenly mixed in a mass ratio of 1:0.3 to 0.5 to obtain dispersed nano-silicon dioxide.
[0018] The enhanced curing agent is specifically: 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine.
[0019] The beneficial effects of the present invention are:
[0020] (1) The present invention uses a specific dibasic acid to modify the epoxy resin and a specific curing agent to cure the epoxy resin, and at the same time compounding the modified nano-silicon dioxide, so as to prepare a mineral casting with a small thermal expansion coefficient, strong temperature resistance, high compressive strength and internal bonding strength, high damping ratio and good shock absorption performance;
[0021] (2) The present invention enhances the heat resistance of epoxy resin by modifying the epoxy resin. Compared with conventional dibasic acids such as sebacic acid, 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid can enhance the heat resistance of epoxy resin and enhance the compressive strength and chemical resistance of epoxy resin due to its stronger coordination effect and greater rigidity. It can also enhance the oxidation resistance of epoxy resin, thereby improving the stability of mineral castings;
[0022] (3) The present invention enhances the compressive strength of mineral castings and the bonding strength between epoxy resin and aggregate by combining a curing agent with a post-curing treatment. Among conventional curing agents, amine curing agents have a fast curing speed, strong volatility, and low heat resistance of the cured resin; anhydride curing agents have strong curing performance, but a high curing temperature and a slow curing speed; phenolic curing agents and isocyanate curing agents have strong curing performance but have a fast curing speed and produce toxic substances. The 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine curing agent selected by the present invention can enhance the strength of mineral castings while effectively enhancing the heat resistance and chemical resistance of mineral castings, further improving the service life of mineral castings. At the same time, its curing speed is moderate, so that the mineral castings can be more uniform in composition during curing and will not have the problem of local overheating, thereby improving the quality and consistency of mineral castings;
[0023] (4) When manufacturing structural parts, it is carried out under high-speed motion or high-load conditions, so vibration will be generated, which will have a negative impact on the stability and reliability of the equipment. Therefore, mineral castings with good shock absorption performance are crucial to improving the precision, surface quality and service life of mechanical processing. At present, the shock absorption performance of mineral castings is mainly achieved by increasing the amount of epoxy resin used, but excessive epoxy resin usage will affect the strength, creep resistance and thermal stability of mineral castings. The present application can effectively enhance the mineral casting after using dibasic acid to modify the epoxy resin and optimizing the curing of the epoxy resin. The strength index of the casting, but the damping ratio and shock absorption effect of the mineral casting will decrease after the strength is improved. Therefore, the damping ratio of the mineral casting is enhanced by adding nano-silicon dioxide. However, since the nano-silicon dioxide has a large specific surface energy and is prone to agglomeration, a silane coupling agent is used to modify it. Compared with conventional silane coupling agents such as γ-aminopropyl triethoxysilane, isopropoxy dioleic acid acyloxy (dioctyl phosphate acyloxy) titanate can improve the dispersibility of nano-silicon dioxide in epoxy resin while improving the adhesion of nano-silicon dioxide in epoxy resin, improve processing fluidity, and thus improve the mechanical strength of the mineral casting;
[0024] (5) The present invention further improves the dispersibility of nano-silica in epoxy resin by compounding a dispersant and nano-silica. Compared with conventional dispersants such as sodium lauryl sulfate, octadecyl polyether stearate has excellent dispersibility and wettability while also having excellent defoaming performance and good anti-foaming effect, which can effectively reduce the amount of bubbles generated during the curing process of epoxy resin, thereby improving the uniformity of the mineral casting components and achieving the purpose of further enhancing the shock absorption performance of the mineral casting. DETAILED DESCRIPTION
[0025] The present invention will be further described in detail below in conjunction with the embodiments.
[0026] Example 1
[0027] Anhydrous ethanol and deionized water are mixed in a volume ratio of 3.5:1 and the pH value is adjusted to 5.5 to obtain a solvent, then 2.5 parts of nano-silica are immersed in the solvent and stirred evenly, then 4.5% of the mass of nano-silica is added with isopropoxy dioleyl (dioctyl phosphate) titanate, the system is heated to 48°C and reacted under 300W ultrasonic conditions for 55 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and octadecyl polyether stearate are evenly mixed in a mass ratio of 1:0.4 to obtain dispersed nano-silica.
[0028] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are mixed uniformly at a mass ratio of 75:25 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0029] 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid and an organic solvent, dimethyl sulfoxide, are uniformly mixed at a mass ratio of 1:25, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0030] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 90.9:9.1, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 0.9% by mass of the catalyst triphenylphosphine of the bisphenol A epoxy resin is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 3 hours, and finally 0.9% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0031] First, 6.6 parts of 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine are dissolved in 7% by mass of dimethyl sulfoxide and stirred evenly, then added into 5.6 parts of modified bisphenol A epoxy resin solution and stirred evenly, then 56.8 parts of granite aggregate and 30 parts of medium sand and gravel filler are added and stirred evenly, then the temperature is raised to 78°C for curing for 8 hours, and the temperature is further raised to 97°C for post-curing treatment for 2.5 hours, then cooled to room temperature for curing for 7.5 hours to obtain a mineral casting.
[0032] Example 2
[0033] Anhydrous ethanol and deionized water are mixed in a volume ratio of 3:1 and the pH value is adjusted to 5.6 to obtain a solvent, then 2 parts of nano-silica are immersed in the solvent and stirred evenly, then 5% of the mass of nano-silica is added with isopropoxy dioleyl acyloxy (dioctyl phosphate acyloxy) titanate, the system is heated to 46°C and reacted under 300W ultrasonic conditions for 60 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and octadecyl polyether stearate are evenly mixed in a mass ratio of 1:0.3 to obtain dispersed nano-silica.
[0034] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are uniformly mixed in a mass ratio of 74:26 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0035] 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid and an organic solvent, dimethyl sulfoxide, are uniformly mixed at a mass ratio of 1:24, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0036] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 90.8:9.2, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 0.8% by mass of the catalyst triphenylphosphine of the bisphenol A epoxy resin is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 3 hours, and finally 1% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0037] First, 6.4 parts of 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine are dissolved in 8% by mass of dimethyl sulfoxide and stirred evenly, then added into 5.8 parts of modified bisphenol A epoxy resin solution and stirred evenly, then 56.6 parts of granite aggregate and 31.2 parts of medium sand and gravel filler are added and stirred evenly, then the temperature is raised to 75°C for curing for 8.5 hours, and the temperature is further raised to 100°C for post-curing treatment for 2 hours, and then cooled to room temperature for curing for 7 hours to obtain a mineral casting.
[0038] Example 3
[0039] Anhydrous ethanol and deionized water are mixed in a volume ratio of 4:1 and the pH value is adjusted to 5.4 to obtain a solvent, then 3 parts of nano-silica are immersed in the solvent and stirred evenly, then 4% of the mass of nano-silica is added with isopropoxy dioleyl acyloxy (dioctyl phosphate acyloxy) titanate, the system is heated to 50°C and reacted under 300W ultrasonic conditions for 50 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and octadecyl polyether stearate are evenly mixed in a mass ratio of 1:0.5 to obtain dispersed nano-silica.
[0040] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are mixed uniformly at a mass ratio of 76:24 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0041] 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid and organic solvent dimethyl sulfoxide are uniformly mixed at a mass ratio of 1:26, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0042] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 91:9, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 1% by mass of the bisphenol A epoxy resin catalyst triphenylphosphine is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 3 hours, and finally 0.8% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0043] First, 6.8 parts of 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine are dissolved in 6% by mass of dimethyl sulfoxide and stirred evenly, then added into 5.4 parts of modified bisphenol A epoxy resin solution and stirred evenly, then 57 parts of granite aggregate and 30.8 parts of medium sand and gravel filler are added and stirred evenly, then the temperature is raised to 80°C for curing for 7.5 hours, then the temperature is further raised to 95°C for post-curing treatment for 3 hours, then cooled to room temperature for curing for 8 hours to obtain a mineral casting.
[0044] Example 4
[0045] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are mixed uniformly at a mass ratio of 75:25 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0046] Sebacic acid and organic solvent dimethyl sulfoxide are mixed evenly at a mass ratio of 1:25, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0047] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 90.9:9.1, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 0.9% by mass of the catalyst triphenylphosphine of the bisphenol A epoxy resin is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 3 hours, and finally 0.9% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0048] The rest is the same as in Example 1.
[0049] Example 5
[0050] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are mixed uniformly at a mass ratio of 75:25 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0051] 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid and an organic solvent, dimethyl sulfoxide, are uniformly mixed at a mass ratio of 1:25, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0052] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 93:7, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 0.9% by mass of the catalyst triphenylphosphine of the bisphenol A epoxy resin is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 3 hours, and finally 0.9% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0053] The rest is the same as in Example 1.
[0054] Example 6
[0055] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are mixed uniformly at a mass ratio of 75:25 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0056] 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid and an organic solvent, dimethyl sulfoxide, are uniformly mixed at a mass ratio of 1:25, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0057] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 90.9:9.1, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 1.5% by mass of the bisphenol A epoxy resin catalyst triphenylphosphine is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 3 hours, and finally 0.9% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0058] The rest is the same as in Example 1.
[0059] Example 7
[0060] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are mixed uniformly at a mass ratio of 75:25 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0061] 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid and an organic solvent, dimethyl sulfoxide, are uniformly mixed at a mass ratio of 1:25, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0062] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 90.9:9.1, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 0.9% by mass of the bisphenol A epoxy resin catalyst triphenylphosphine is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 2 hours, and finally 0.9% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0063] The rest is the same as in Example 1.
[0064] Example 8
[0065] First, add 6.4 parts of triethylenetetramine into 5.8 parts of modified bisphenol A epoxy resin solution and stir evenly, then add 56.6 parts of granite aggregate and 31.2 parts of medium sand and gravel filler and stir evenly, then heat to 75°C for curing for 8.5 hours, continue to heat to 100°C for post-curing treatment for 2 hours, then cool to room temperature and cure for 7 hours to obtain a mineral casting.
[0066] The rest is the same as Example 2.
[0067] Example 9
[0068] First, 6.4 parts of 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine are dissolved in 3% by weight of dimethyl sulfoxide and stirred evenly, then added into 5.8 parts of modified bisphenol A epoxy resin solution and stirred evenly, then 56.6 parts of granite aggregate and 31.2 parts of medium sand and gravel filler are added and stirred evenly, then the temperature is raised to 75°C for curing for 8.5 hours, and the temperature is further raised to 100°C for post-curing treatment for 2 hours, and then cooled to room temperature for curing for 7 hours to obtain a mineral casting.
[0069] The rest is the same as Example 2.
[0070] Example 10
[0071] First, 6.4 parts of 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine are dissolved in 8% by mass of dimethyl sulfoxide and stirred evenly, then added into 5.8 parts of modified bisphenol A epoxy resin solution and stirred evenly, then 56.6 parts of granite aggregate and 31.2 parts of medium sand and gravel filler are added and stirred evenly, then the temperature is raised to 75°C for curing for 10.5 hours, then cooled to room temperature for curing for 7 hours to obtain a mineral casting.
[0072] The rest is the same as Example 2.
[0073] Embodiment 11
[0074] Anhydrous ethanol and deionized water are mixed in a volume ratio of 4:1 and the pH value is adjusted to 5.4 to obtain a solvent, then 3 parts of nano-silica are immersed in the solvent and stirred evenly, then 4% of γ-aminopropyltriethoxysilane by mass of the nano-silica is added, the system is heated to 50°C and reacted under 300W ultrasonic conditions for 50 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and octadecyl polyether stearate are evenly mixed in a mass ratio of 1:0.5 to obtain dispersed nano-silica.
[0075] The rest is the same as in Example 3.
[0076] Example 12
[0077] Anhydrous ethanol and deionized water are mixed in a volume ratio of 4:1 and the pH value is adjusted to 5.4 to obtain a solvent, then 3 parts of nano-silica are immersed in the solvent and stirred evenly, then 4% of the mass of nano-silica is added with isopropoxy dioleyl acyloxy (dioctyl phosphate acyloxy) titanate, the system is heated to 50°C and reacted under 300W ultrasonic conditions for 50 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and sodium dodecyl sulfate are evenly mixed in a mass ratio of 1:0.5 to obtain dispersed nano-silica.
[0078] The rest is the same as in Example 3.
[0079] Example 13
[0080] Anhydrous ethanol and deionized water are mixed in a volume ratio of 4:1 and the pH value is adjusted to 6.2 to obtain a solvent, then 3 parts of nano-silica are immersed in the solvent and stirred evenly, then 4% of the mass of nano-silica is added with isopropoxy dioleyl acyloxy (dioctyl phosphate acyloxy) titanate, the system is heated to 50°C and reacted under 300W ultrasonic conditions for 50 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and octadecyl polyether stearate are evenly mixed in a mass ratio of 1:0.5 to obtain dispersed nano-silica.
[0081] The rest is the same as in Example 3.
[0082] Embodiment 14
[0083] Anhydrous ethanol and deionized water are mixed in a volume ratio of 4:1 and the pH value is adjusted to 5.4 to obtain a solvent, then 3 parts of nano-silica are immersed in the solvent and stirred evenly, then 4% of the mass of nano-silica by weight of isopropoxy dioleyl (dioctyl phosphate) titanate is added, the system is heated to 50°C and reacted under 150W ultrasonic conditions for 50 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and octadecyl polyether stearate are evenly mixed in a mass ratio of 1:0.5 to obtain dispersed nano-silica.
[0084] The rest is the same as in Example 3.
[0085] Embodiment 15
[0086] Anhydrous ethanol and deionized water are mixed in a volume ratio of 4:1 and the pH value is adjusted to 5.4 to obtain a solvent, then 3 parts of nano-silica are immersed in the solvent and stirred evenly, then 4% of the mass of nano-silica is added with isopropoxy dioleyl acyloxy (dioctyl phosphate acyloxy) titanate, the system is heated to 50°C and reacted under 300W ultrasonic conditions for 50 minutes, after the reaction, it is washed with anhydrous ethanol and dried to obtain modified nano-silica, and then the modified nano-silica and octadecyl polyether stearate are evenly mixed in a mass ratio of 1:0.2 to obtain dispersed nano-silica.
[0087] The rest is the same as in Example 3.
[0088] Example 16
[0089] The bisphenol A epoxy resin and the active diluent octyl glycidyl ether are mixed uniformly at a mass ratio of 76:24 to obtain a low-viscosity bisphenol A epoxy resin solution;
[0090] 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid and organic solvent dimethyl sulfoxide are uniformly mixed at a mass ratio of 1:26, and a dibasic acid solution is obtained after the dibasic acid is completely dissolved;
[0091] A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 91:9, put into a flask and placed in a magnetically controlled stirring oil bath for uniform mixing, 1% by mass of the bisphenol A epoxy resin catalyst triphenylphosphine is added at 100° C. and slowly stirred until uniform, then the temperature is raised to 130° C. and slowly stirred for reaction for 3 hours, and finally 0.5% by mass of the bisphenol A epoxy resin dispersed nano-silica is added to obtain a modified bisphenol A epoxy resin solution.
[0092] test:
[0093] Various performance indicators of the mineral castings prepared in Examples 1 to 16 were measured, where a is the thermal expansion coefficient, b is the compressive strength, c is the tensile strength, and d is the damping ratio. Specific data are shown in Table 1.
[0094] Table 1 Performance data of mineral castings of Example 1 to Example 16
[0095]
[0096]
[0097] It can be seen from Table 1 that the performance data of the mineral castings prepared in Examples 1 to 3 are all at the optimal level, indicating that their process parameters are the optimal parameters; Example 4 replaces 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid with sebacic acid, so its thermal expansion coefficient is significantly increased compared with Example 1, and the temperature resistance of the mineral casting is significantly weakened. At the same time, since the rigidity of sebacic acid is not as good as that of 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid, it also has a certain effect on the compressive strength and flexural strength of the mineral casting; the reason why the performance data of the mineral casting in Example 5 is not as good as that in Example 1 may be that the proportion of the dibasic acid used is reduced, which reduces the modification effect of the epoxy resin; the reason why the performance data of the mineral casting in Example 6 is not as good as that in Example 1 may be that the amount of catalyst used is too much, The reaction rate is reduced, thereby affecting the modification effect; the reason why the performance data of the mineral casting in Example 7 is not as good as that in Example 1 may be that the modification reaction time is shorter, so the modification effect is worse; the reason why the performance data of the mineral casting in Example 8 is not as good as that in Example 2 may be that after 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine is replaced by triethylenetetramine, on the one hand, the reaction rate of triethylenetetramine is faster and more heat is released, so the uniformity of its components after curing will be worse and more bubbles will be generated, which will affect the strength and damping ratio of the mineral casting, on the other hand, the heat resistance of the resin after curing with the fatty amine curing agent is worse, so its thermal expansion coefficient will be larger; Performance data of mineral casting in Example 9 The reason why the performance data of the mineral casting in Example 10 is not as good as that in Example 2 may be that the solvent used in the curing agent is too little, and part of the curing agent is not completely dissolved, thus affecting the subsequent curing process; the reason why the performance data of the mineral casting in Example 10 is not as good as that in Example 2 may be that no high-temperature post-curing treatment is performed, and the curing and cross-linking effect inside the mineral casting will be worse; the reason why the performance data of the mineral casting in Example 11 is not as good as that in Example 3 may be that after replacing isopropoxy dioleyl (dioctyl phosphate) titanate with γ-aminopropyl triethoxy silane, on the one hand, the effect of γ-aminopropyl triethoxy silane in enhancing dispersibility is not as good as that of isopropoxy dioleyl (dioctyl phosphate) titanate, and on the other hand, γ-aminopropyl triethoxy silane does not have the effect of enhancing the bonding effect and flowability of the mineral casting components. The reason why the performance data of the mineral casting in Example 12 is not as good as that in Example 3 may be that after replacing octadecyl polyether stearate with sodium lauryl sulfate, although sodium lauryl sulfate has good dispersibility, it also has excellent foaming performance, which will greatly increase the number of bubbles inside the epoxy resin. Therefore, the damping ratio of the mineral casting in Example 12 is the lowest; the reason why the performance data of the mineral casting in Example 13 is not as good as that in Example 3 may be that the pH value of the hydrolysis of the silane coupling agent is too high, which affects its hydrolysis degree and also affects the subsequent modification effect; the reason why the performance data of the mineral casting in Example 14 is not as good as that in Example 3 may be that the ultrasonic power is too low, and some nano-silicon dioxide is not completely dispersed, which affects the modification effect of this part of nano-silicon dioxide;The reason why the performance data of the mineral casting in Example 15 is not as good as that in Example 3 may be that the amount of octadecyl polyether stearate used is less, which affects the subsequent defoaming effect and the dispersibility of nano-silicon dioxide; the reason why the performance data of the mineral casting in Example 16 is not as good as that in Example 3 may be that the amount of dispersed nano-silicon dioxide used is lower, which also affects the various performance data of the mineral casting. ;
Claims
1. A mineral casting prepared based on modified epoxy resin, characterized in that: Contains the following components by mass: 5.4-5.8 parts of modified bisphenol A epoxy resin solution, 6.4-6.8 parts of enhanced curing agent, 56.6-57 parts of aggregate, 30.8-31.2 parts of filler; The specific preparation steps are: Firstly, the enhanced curing agent is dissolved in 6% to 8% of dimethyl sulfoxide by weight and stirred evenly, then added into the modified bisphenol A epoxy resin solution and stirred evenly, then the aggregate and filler are added and stirred evenly, then the temperature is raised to 75 to 80°C for curing for 7.5 to 8.5 hours, then the temperature is further raised to 95 to 100°C for post-curing treatment for 2 to 3 hours, then the mineral casting is obtained after cooling to room temperature for curing for 7 to 8 hours.
2. A mineral casting prepared based on modified epoxy resin according to claim 1, characterized in that: The preparation steps of the modified bisphenol A epoxy resin solution are: (1) mixing bisphenol A epoxy resin and active diluent octyl glycidyl ether in a mass ratio of 74-76:24-26 to obtain a low-viscosity bisphenol A epoxy resin solution; (2) mixing the dibasic acid and the organic solvent dimethyl sulfoxide in a mass ratio of 1:24-26, and obtaining a dibasic acid solution after the dibasic acid is completely dissolved; (3) A low-viscosity bisphenol A epoxy resin solution and a dibasic acid solution are mixed in a mass ratio of 90.8-91:9-9.2, and the mixture is placed in a flask and placed in a magnetically controlled stirring oil bath for uniform mixing. At 100° C., 0.8% to 1% by mass of the catalyst triphenylphosphine of the bisphenol A epoxy resin is added and slowly stirred until uniform. The mixture is then heated to 130° C. and slowly stirred for reaction for 3 hours. Finally, 0.8% to 1% by mass of the dispersed nano-silica of the bisphenol A epoxy resin is added to obtain a modified bisphenol A epoxy resin solution.
3. A mineral casting prepared based on modified epoxy resin as claimed in claim 2, characterized in that: The dibasic acid is specifically: 1,5-dihydroxynaphthalene-2,6-dicarboxylic acid.
4. A mineral casting prepared based on modified epoxy resin as claimed in claim 2, characterized in that: The preparation method of dispersed nano silicon dioxide is: Anhydrous ethanol and deionized water are mixed in a volume ratio of 3 to 4:1 and the pH value is adjusted to 5.4 to 5.6 to obtain a solvent, then 2 to 3 parts by mass of nano-silicon dioxide are immersed in the solvent and stirred evenly, then 4% to 5% by mass of isopropoxy dioleic acid acyloxy (dioctyl phosphate acyloxy) titanate is added, the system is heated to 46 to 50°C and reacted under 300W ultrasonic conditions for 50 to 60 minutes, after the reaction, the modified nano-silicon dioxide is washed with anhydrous ethanol and dried to obtain modified nano-silicon dioxide, and then the modified nano-silicon dioxide and octadecyl alcohol polyether stearate are evenly mixed in a mass ratio of 1:0.3 to 0.5 to obtain dispersed nano-silicon dioxide.
5. A mineral casting prepared based on modified epoxy resin according to claim 1, characterized in that: The enhanced curing agent is specifically: 2,4-diamino-6-[2-(2-undecyl-1-imidazolyl)ethyl]-1,3,5-thiazine.
Citation Information
Cited By
Detection method and application of phase of refractory material
CN120891028A